Tinjauan Yuridis Perlindungan Hukum Korban Tindak Pidana Pemerkosaan Yang Menderita Gangguan Kejiwaan Berdasarkan Undang-Undang Nomor 31 Tahun 2014 Tentang Perubahan Undang- Undang Nomor 13 Tahun 2006 Tentang Perlindungan Saksi dan Korban - Karina, Gerith; Firdaus, Emilda; R, Mukhlis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Errors of Practice (malpractice) occur or caused a malfunction that can be less cautious, less careful, and less seriousness in the anamnesis, examination, diagnosis, therapy/treatment and follow-up, on the other side because it is less skilled and lack of knowledge from the healthcare personnel concerned. The study titled